IL-35: A Novel Immunomodulator in Hepatitis B Virus-Related Liver Diseases - Li, Xuefen; Liu, Xia; Wang, Weilin (Frontiers in Cell and Developmental Biology, 2021)
Chronic hepatitis B virus (HBV) infection is a risk factor for liver cirrhosis (LC) and hepatocellular carcinoma (HCC), however, little is known about the mechanisms involved in the progression of HBV-related diseases. It has been well acknowledged that host immune response was closely related to the clinical outcomes of patients with HBV infection. As the factors closely related to the immunomodulatory process, cytokines are crucial in the cell-cell communication and the host responses to HBV infection. Recently, a newly discovered cytokine, designated as interleukin-35 (IL-35), has been proved to be essential for the progression of chronic HBV infection, the development of cirrhosis, the transformation of cirrhosis to HCC, and the metastasis of HCC. Specifically, it showed various biological activities such as inhibiting the HBV-specific cytotoxic T lymphocyte (CTL) proliferation and cytotoxicity, deactivating the immature effector T-cells (Teffs), as well as delaying the proliferation of dendritic cells. It regulated the immune responses by acting as a "brake" on the activation of Teffs, which subsequently played important roles in the pathogenesis of various inflammatory diseases and malignancies. In this review, we focused on the most recent data on the relationship between IL-35 and chronic HBV infection, LC and HCC.